Innovating teachers' professional learning through digital technologies - Minea-Pic, Andreea (OECD Publishing, 2020)
Digital technologies offer immense potential for transforming teacher learning and the delivery of professional development activities throughout teachers' careers. As the COVID-19 pandemic has made face‑to‑face professional learning challenging or impossible for teachers to attend in many contexts, online professional learning options for teachers have been receiving renewed attention. This paper puts forward research evidence on the effectiveness of various forms of online learning for teachers and adults, and examines prerequisite conditions for enhancing teacher learning through digital technologies. Teachers' engagement in online learning activities, as captured by OECD surveys, remained limited in many OECD countries before the COVID-19 pandemic. This paper provides a basis for investigating how policies can support teachers' engagement in professional learning using digital technologies and help strike a balance between system-level provision of online teacher professional learning opportunities and the facilitation of teacher-led initiatives
Keywords: Education